Land, Dorf, Kehilla "Landjudentum" in der deutschen und deutsch-jüdischen Erzählliteratur bis 1918 - Laufer, Almut (Conditio Judaica, 2020)
For secular, well-educated society, the "countryside" has always been a projection screen for desires and aversions. Almut Laufer examines the narrative traces left by rural Jewish communities by considering the texts of non-Jewish authors of the late Enlightenment and Counter-Enlightenment and the stories of Jewish authors of the 19th and early 20th centuries that reflect inner Jewish discourse.